Conductive silver paste for low temperature co-fired ceramic substrate and preparation method thereof

By using composite silver powder, organic carrier and silver resin acid components in low-temperature cofired ceramic substrates, the problems of conductivity and cost are solved, and high performance and low cost are achieved.

CN119008076BActive Publication Date: 2025-02-11SHENZHEN SHENYUNJI NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411418677.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-11
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

It is difficult for existing conductive silver paste to take into account both good conductivity and low-price in low-temperature co-fired ceramic substrates, and during the sintering process, performance is easily degraded due to the difference in affinity between the silver powder and the substrate.

Method used

Composite silver powder, organic carrier and silver resin acid salt are used to prepare conductive silver paste for low-temperature co-fired ceramic substrates through specific proportions and treatment methods to form conductive paths and improve the advantages of the sintering network.

Benefits of technology

It reduces the production cost of conductive silver paste, improves the conductivity and adhesion, reduces the internal cracking and layering of the device caused by insufficient interface bonding force, and enhances the overall performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of conductive pastes, and in particular to a conductive silver paste for a low-temperature co-fired ceramic substrate and a preparation method thereof. The conductive silver paste comprises the following raw materials in parts by weight: 40-60 parts of composite silver powder, 26-55 parts of an organic carrier, 2-5 parts of a solvent, 0.5-5 parts of an inorganic additive, 0.5-2 parts of a plasticizer, and 0.5-2 parts of a thixotropic agent. The content of silver powder in the conductive silver paste for a low-temperature co-fired ceramic substrate provided by the invention is much lower than that in the conventional prior art, which greatly reduces the production cost. In addition, due to the introduction of silver resinate in the silver powder, the performance degradation caused by the difference in affinity between the silver powder and the substrate during the sintering process is effectively reduced. The introduction of the silver resinate and the compounding of silver nanowires, silver nanosheets and silver nanoparticles of different dimensions also reduce the sintering temperature of the conductive silver paste, so that the conductive silver paste finally prepared has good hardness and adhesion as well as good conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive pastes, and in particular to a conductive silver paste for a low-temperature co-fired ceramic substrate and a preparation method thereof. Background Art

[0002] With the rapid development of modern information technology, there is a demand for miniaturization, convenience, multi-function and high reliability of electronic products. LTCC (Low Temperature Co-fired Ceramic) technology is an advanced passive integrated and hybrid circuit. It can encapsulate the three major passive components (including resistors, capacitors and inductors) and various passive components (such as filters, transformers, etc.) in a multi-layer wiring substrate, and integrate them with active devices (such as power MOS, transistors, IC circuit modules, etc.) into a complete circuit system. Low temperature co-fired ceramic technology is an impressive integrated component technology developed in recent years. Because it can meet the above requirements of electronic products, it has become the first choice for the integration and modularization of electronic components in the future. As the design basis for high-performance and low-energy devices, the research and development of LTCC technology and related materials has great application value. Conductive silver paste is a type of precious metal electronic paste, which is made of silver powder, organic carrier, inorganic or polymer binder through stirring and rolling. Conductive silver paste is currently the most important and most in-demand type of electronic paste, and it has an irreplaceable position in the field of electronics. Because conductive silver paste has good conductivity, solderability and reliability, it is widely used in touch screens, solar cell electrodes, flexible sensors, multilayer ceramic capacitors, filters, packaging circuits and other fields.

[0003] Nowadays, in order to reduce the sintering temperature, low-temperature co-firing technology usually uses low-melting oxides or low-melting glass to achieve ceramics. The complex system makes it difficult for traditional silver paste to match it, and even cannot meet the basic use requirements. During the co-firing process of traditional conductive silver paste and low-temperature co-fired ceramic substrate, due to the difference in affinity between ceramics and silver powder and between silver powder and silver powder, the silver powder diffuses excessively into the porcelain body, causing the insulation resistance to decrease, and there is a risk of electrical breakdown of the circuit. It also causes the silver electrode layer to be prone to more voids after sintering; and the insufficient bonding force between the silver layer and the ceramic interface will lead to serious consequences of cracking and stratification inside the device. In addition, in order to increase the conductivity of the conductive silver paste in the prior art, the amount of silver powder is generally increased, but due to the high price of silver powder, the production cost is also greatly increased.

[0004] Therefore, according to the above-mentioned related technologies, it is urgent to develop a conductive silver paste for low-temperature co-fired ceramic substrate and a preparation method thereof. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a conductive silver paste for a low-temperature co-fired ceramic substrate and a preparation method thereof, so as to solve the problem that the conductive silver paste produced in the prior art is difficult to achieve both good conductivity and low price.

[0006] Based on the above purpose, the present invention provides a conductive silver paste for a low-temperature co-fired ceramic substrate and a preparation method thereof.

[0007] A conductive silver paste for a low-temperature co-fired ceramic substrate comprises the following raw materials in parts by weight: 40-60 parts of composite silver powder, 26-55 parts of an organic carrier, 2-5 parts of a solvent, 0.5-5 parts of an inorganic additive, 0.5-2 parts of a plasticizer, and 0.5-2 parts of a thixotropic agent;

[0008] The composite silver powder is nano silver powder and silver resinate in a mass ratio of 32-51:8-9;

[0009] The nano silver powder is obtained by mixing nano silver wires, nano silver flakes and nano silver particles in a mass ratio of 7-14:23-33:2-4;

[0010] The silver resinate is obtained by mixing silver neodecanoate, silver neopentanoate and silver butyrate in a mass ratio of 4-5:3.5-4:0.5-1;

[0011] The organic carrier is obtained by mixing polyether polyurethane silver resin, waterborne polyurethane resin and waterborne acrylate resin in a mass ratio of 12-22:10-20:4-13.

[0012] Preferably, the preparation method of the polyether polyurethane silver resin is as follows:

[0013] 45-50 g of polyether polyurethane resin was added to 38-40 mL of butyl acetate, and the mixture was mechanically stirred for 20 min. 1-1.5 mL of an aqueous solution of silver nitrate was added, and the mixture was stirred for 30 min to obtain a polyether polyurethane silver resin.

[0014] Preferably, the aqueous solution of silver nitrate is prepared by adding 0.2-0.4 g of silver nitrate into 1-1.5 mL of 75-80° C. deionized water.

[0015] Preferably, the preparation method of the silver neodecanoate is as follows:

[0016] Step A1. Dissolve sodium hydroxide in deionized water to obtain a mixed solution A1;

[0017] Step A2. dissolving neodecanoic acid in methanol to obtain a mixed solution A2;

[0018] Step A3. Dissolve silver nitrate in deionized water to obtain a mixed solution A3;

[0019] Step A4. Add the mixed solution A1 to the mixed solution A2, stir and react at room temperature for 30 minutes, then add the mixed solution A3, stir for another 30 minutes, filter, wash with ethanol 3-5 times, and place in a vacuum oven at 60°C to dry in the dark for 10-12 hours to obtain a silver neodecanoate precursor;

[0020] Step A5. xylene, pineol and silver neodecanoate precursor are placed in a glass bottle, and finally the obtained solution is filtered through a 200 μm syringe filter to obtain silver neodecanoate.

[0021] Preferably, the ratio of sodium hydroxide to deionized water in step A1 is 2-3 g: 45-55 mL;

[0022] The ratio of neodecanoic acid to methanol in step A2 is 8-12 g: 45-55 mL;

[0023] The usage ratio of silver nitrate and deionized water in step A3 is 9-10 g:48-52 mL;

[0024] In step A4, the volume ratio of the mixed solution A1, the mixed solution A2 and the mixed solution A3 is 45-55:45-55:48-52;

[0025] The mass ratio of xylene, terpineol and silver neodecanoate precursor in step A5 is 2-3:2-3:5.5-6.5.

[0026] Preferably, the preparation method of the silver pivalate is as follows:

[0027] Step B1. Dissolve sodium hydroxide in deionized water to obtain a mixed solution B1;

[0028] Step B2. dissolving pivalic acid in methanol to obtain a mixed solution B2;

[0029] Step B3. Dissolve silver nitrate in deionized water to obtain a mixed solution B3;

[0030] Step B4. Add the mixed solution A to the mixed solution B, stir and react at room temperature for 30 minutes, then add the mixed solution C, stir for another 30 minutes, filter, wash with ethanol 3-5 times, and place in a vacuum oven at 60° C. to dry in the dark for 10-12 hours to obtain a silver pivalate precursor;

[0031] Step B5. xylene, pinene alcohol and silver pivalate precursor are placed in a glass bottle, and finally the obtained solution is filtered through a 200 μm syringe filter to obtain silver pivalate.

[0032] Preferably, the ratio of sodium hydroxide to deionized water in step B1 is 2-3 g: 45-55 mL;

[0033] The ratio of pivalic acid to methanol in step B2 is 8-12 g: 45-55 mL;

[0034] The usage ratio of silver nitrate and deionized water in step B3 is 9-10 g: 48-52 mL;

[0035] In step B4, the volume ratio of the mixed solution B1, the mixed solution B2 and the mixed solution B3 is 45-55:45-55:48-52;

[0036] The mass ratio of xylene, terpineol and silver pivalate precursor in step B5 is 2-3:2-3:5.5-6.5.

[0037] Preferably, the preparation method of the silver n-butyrate is as follows:

[0038] Step C1. dissolving sodium hydroxide in deionized water to obtain a mixed solution C1;

[0039] Step C2. dissolving n-butyric acid in methanol to obtain a mixed solution C2;

[0040] Step C3. dissolving silver nitrate in deionized water to obtain a mixed solution C3;

[0041] Step C4. Add the mixed solution C1 to the mixed solution C2, stir and react at room temperature for 30 minutes, then add the mixed solution C3, stir for another 30 minutes, filter, wash with ethanol 3-5 times, and place in a vacuum oven at 60° C. to dry in the dark for 10-12 hours to obtain a silver butyrate precursor;

[0042] Step C5. xylene, pinene alcohol and silver butyrate precursor are placed in a glass bottle, and finally the obtained solution is filtered through a 200 μm syringe filter to obtain silver butyrate.

[0043] Preferably, the ratio of sodium hydroxide to deionized water in step C1 is 2-3 g: 45-55 mL;

[0044] The usage ratio of n-butyric acid and methanol in step C2 is 8-12 g: 45-55 mL;

[0045] The usage ratio of silver nitrate and deionized water in step C3 is 9-10 g: 48-52 mL;

[0046] In step C4, the volume ratio of the mixed solution C1, the mixed solution C2 and the mixed solution C3 is 45-55:45-55:48-52;

[0047] The mass ratio of xylene, terpineol and silver butyrate precursor in step C5 is 2-3:2-3:5.5-6.5.

[0048] Preferably, the average diameter of the silver nanowire is 58-60 nm and the aspect ratio is 175;

[0049] The size of the nano silver flakes is 2-3 μm;

[0050] The average particle size of the nano silver particles is 3.8-4 nm.

[0051] Preferably, the solvent is any one of diethylene glycol ethyl ether, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, diethylene glycol ethyl ether acetate and terpineol;

[0052] The inorganic additive is any one of magnesium oxide, titanium dioxide, copper oxide, zinc oxide and aluminum oxide;

[0053] The plasticizer is tributyl citrate; and the thixotropic agent is polyamide wax.

[0054] A method for preparing a conductive silver paste for a low temperature co-fired ceramic substrate comprises the following steps:

[0055] The composite silver powder, organic carrier, solvent, inorganic additive, plasticizer and thixotropic agent are mixed, ground, and materials with a fineness of less than 10 μm are collected to obtain a conductive silver paste for a low-temperature co-fired ceramic matrix.

[0056] Beneficial effects of the present invention:

[0057] The content of silver powder in the conductive silver paste for low-temperature co-fired ceramic substrate provided by the present invention is much lower than that in the conventional prior art, which greatly reduces the production cost. In addition, due to the introduction of silver resinate in the silver powder, the performance degradation caused by the difference in affinity between the silver powder and the substrate during the sintering process is effectively reduced.

[0058] The silver powder provided by the present invention introduces silver resinate, which is thermally decomposed during the sintering process. The thermal decomposition product cooperates with the nano silver powder to form a conductive path through accumulation and fusion, thereby greatly reducing the sintering temperature of the conductive silver paste. In addition, by mixing silver nanowires, silver nanosheets and silver nanoparticles of different dimensions in specific proportions, the conductive silver paste finally prepared has good hardness and adhesion, and also has good conductive performance.

[0059] The silver resinate provided by the present invention introduces silver neodecanoate, silver pivalate and silver butyrate mixed in a specific ratio, wherein the compounding of long-chain silver resinate and short-chain silver resinate, and the compounding of straight-chain silver resinate and branched-chain silver resinate enable the formation of an excellent sintering network and a larger grain size during the sintering process, thereby further increasing the conductive performance of the conductive silver paste.

[0060] The organic carrier provided by the present invention is compounded with polyether polyurethane silver resin, waterborne polyurethane resin and waterborne acrylate resin, which can effectively increase the affinity between silver powder and the matrix, and at the same time increase the adhesion of the conductive silver paste, effectively reduce the cracking and delamination inside the device caused by insufficient bonding force between interfaces, and thus reduce safety hazards. DETAILED DESCRIPTION

[0061] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0062] The sources and properties of some of the raw materials used in the present invention are as follows:

[0063] The polyether polyurethane resin was industrial pure and purchased from Jiangyin Huashi Chemical Additive Co., Ltd.

[0064] Embodiment 1: A method for preparing a conductive silver paste for a low temperature co-fired ceramic substrate, comprising the following steps:

[0065] S1. Dissolve 2 g of sodium hydroxide in 45 mL of deionized water to obtain a mixed solution A1;

[0066] S2. 8 g of neodecanoic acid was dissolved in 45 mL of methanol to obtain a mixed solution A2;

[0067] S3. Dissolve 9 g of silver nitrate in 48 mL of deionized water to obtain a mixed solution A3;

[0068] S4. 45 mL of the mixed solution A1 was added to 45 mL of the mixed solution A2, and the mixture was stirred at room temperature for 30 min, and then 48 mL of the mixed solution A3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol three times, the mixture was placed in a vacuum oven at 60 ° C and dried in the dark for 10 h to obtain a silver neodecanoate precursor;

[0069] S5. 2 g of xylene, 2 g of pineol and 5.5 g of silver neodecanoate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver neodecanoate;

[0070] S6. Dissolve 2 g of sodium hydroxide in 45 mL of deionized water to obtain a mixed solution B1;

[0071] S7. Dissolve 8 g of pivalic acid in 45 mL of methanol to obtain a mixed solution B2;

[0072] S8. Dissolve 9 g of silver nitrate in 48 mL of deionized water to obtain a mixed solution B3;

[0073] S9. 45 mL of mixed solution B1 was added to 45 mL of mixed solution B2, and the mixture was stirred at room temperature for 30 min. Then 48 mL of mixed solution B3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol for 3 times, the mixture was placed in a vacuum oven at 60° C. and dried in the dark for 10 h to obtain a silver pivalate precursor.

[0074] S10. 2 g of xylene, 2 g of terpineol and 5.5 g of silver pivalate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver pivalate;

[0075] S11. Dissolve 2 g of sodium hydroxide in 45 mL of deionized water to obtain a mixed solution C1;

[0076] S12. 8 g of n-butyric acid was dissolved in 45 mL of methanol to obtain a mixed solution C2;

[0077] S13. Dissolve 9 g of silver nitrate in 48 mL of deionized water to obtain a mixed solution C3;

[0078] S14. 45 mL of mixed solution C1 was added to 45 mL of mixed solution C2, and the mixture was stirred at room temperature for 30 min. Then 48 mL of mixed solution C3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol for 3 times, the mixture was placed in a vacuum oven at 60 ° C and dried in the dark for 10 h to obtain a silver butyrate precursor.

[0079] S15. 2 g of xylene, 2 g of pineol and 5.5 g of silver butyrate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver butyrate;

[0080] S16. 4 g of silver neodecanoate, 3.5 g of silver neopentanoate and 0.5 g of silver n-butyrate were mixed to obtain silver resinate;

[0081] S17. 7 g of silver nanowires having an average diameter of 58 nm and an aspect ratio of 175, 23 g of silver nanosheets having a size of 2 μm, and 2 g of silver nanoparticles having an average particle size of 3.8 nm were mixed to obtain silver nanoparticles;

[0082] S18. Mixing 32 g of nano silver powder and 8 g of silver resinate to obtain a composite silver powder;

[0083] S19. 0.2 g of silver nitrate was added to 1 mL of 75° C. deionized water to prepare an aqueous solution of silver nitrate, 45 g of polyether polyurethane resin was added to 38 mL of butyl acetate, mechanically stirred for 20 min, 1 mL of the aqueous solution of silver nitrate was added, and stirred for 30 min to obtain a polyether polyurethane silver resin;

[0084] S20. 12 g of a polyether polyurethane silver resin, 10 g of an aqueous polyurethane resin and 4 g of an aqueous acrylate were mixed to obtain an organic carrier;

[0085] S21. 40 g of composite silver powder, 26 g of organic carrier, 2 g of diethylene glycol ethyl ether, 0.5 g of magnesium oxide, 0.5 g of tributyl citrate and 0.5 g of polyamide wax are mixed, ground, and materials with a fineness of less than 10 μm are collected to obtain a conductive silver paste for a low-temperature co-fired ceramic substrate.

[0086] Embodiment 2: A method for preparing a conductive silver paste for a low temperature co-fired ceramic substrate, comprising the following steps:

[0087] S1. Dissolve 2.2 g of sodium hydroxide in 49 mL of deionized water to obtain a mixed solution A1;

[0088] S2. Dissolve 9 g of neodecanoic acid in 47 mL of methanol to obtain a mixed solution A2;

[0089] S3. Dissolve 9.2 g of silver nitrate in 49 mL of deionized water to obtain a mixed solution A3;

[0090] S4. 47 mL of the mixed solution A1 was added to 47 mL of the mixed solution A2, and the mixture was stirred at room temperature for 30 min, and then 49 mL of the mixed solution A3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol 4 times, the mixture was placed in a vacuum oven at 60 ° C and dried in the dark for 11 h to obtain a silver neodecanoate precursor;

[0091] S5. 2.2 g of xylene, 2.2 g of pineol and 5.7 g of silver neodecanoate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver neodecanoate;

[0092] S6. Dissolve 2.2 g of sodium hydroxide in 47 mL of deionized water to obtain a mixed solution B1;

[0093] S7. Dissolve 9 g of pivalic acid in 47 mL of methanol to obtain a mixed solution B2;

[0094] S8. Dissolve 9.2 g of silver nitrate in 49 mL of deionized water to obtain a mixed solution B3;

[0095] S9. 47 mL of mixed solution B1 was added to 47 mL of mixed solution B2, and the mixture was stirred at room temperature for 30 min. Then 49 mL of mixed solution B3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol for 4 times, the mixture was placed in a vacuum oven at 60° C. and dried in the dark for 11 h to obtain a silver pivalate precursor.

[0096] S10. 2.2 g of xylene, 2.2 g of terpineol and 5.7 g of silver pivalate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver pivalate;

[0097] S11. Dissolve 2.2 g of sodium hydroxide in 47 mL of deionized water to obtain a mixed solution C1;

[0098] S12. 9 g of n-butyric acid was dissolved in 47 mL of methanol to obtain a mixed solution C2;

[0099] S13. Dissolve 9.2 g of silver nitrate in 49 mL of deionized water to obtain a mixed solution C3;

[0100] S14. 47 mL of mixed solution C1 was added to 47 mL of mixed solution C2, and the mixture was stirred at room temperature for 30 min. Then 49 mL of mixed solution C3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol for 4 times, the mixture was placed in a vacuum oven at 60 ° C and dried in the dark for 11 h to obtain a silver butyrate precursor;

[0101] S15. 2.2 g of xylene, 2.2 g of pinene alcohol and 5.7 g of silver butyrate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver butyrate;

[0102] S16. 4.2 g of silver neodecanoate, 3.7 g of silver neopentanoate and 0.7 g of silver n-butyrate were mixed to obtain silver resinate;

[0103] S17. 12.5 g of silver nanowires having an average diameter of 59 nm and an aspect ratio of 175, 32.5 g of silver nanosheets having a size of 2.5 μm, and 3.5 g of silver nanoparticles having an average particle size of 3.9 nm were mixed to obtain silver nanoparticles;

[0104] S18. Mixing 48 g of nano silver powder and 8.2 g of silver resinate to obtain a composite silver powder;

[0105] S19. 0.25 g of silver nitrate was added to 1.1 mL of 76° C. deionized water to prepare an aqueous solution of silver nitrate, 46 g of polyether polyurethane resin was added to 39 mL of butyl acetate, mechanically stirred for 20 min, 1.1 mL of silver nitrate aqueous solution was added, and stirred for 30 min to obtain a polyether polyurethane silver resin;

[0106] S20. 14 g of a polyether polyurethane silver resin, 12 g of an aqueous polyurethane resin and 6 g of an aqueous acrylate were mixed to obtain an organic carrier;

[0107] S21. 56 g of composite silver powder, 30 g of organic carrier, 3 g of diethylene glycol ethyl ether, 3 g of magnesium oxide, 1.2 g of tributyl citrate and 1.2 g of polyamide wax are mixed, ground, and materials with a fineness of less than 10 μm are collected to obtain a conductive silver paste for a low-temperature co-fired ceramic substrate.

[0108] Embodiment 3: A method for preparing a conductive silver paste for a low temperature co-fired ceramic substrate, comprising the following steps:

[0109] S1. Dissolve 2.4 g of sodium hydroxide in 49 mL of deionized water to obtain a mixed solution A1;

[0110] S2. Dissolve 10 g of neodecanoic acid in 49 mL of methanol to obtain a mixed solution A2;

[0111] S3. Dissolve 9.6 g of silver nitrate in 50 mL of deionized water to obtain a mixed solution A3;

[0112] S4. 49 mL of mixed solution A1 was added to 49 mL of mixed solution A2, and the mixture was stirred at room temperature for 30 min, and then 50 mL of mixed solution A3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol for 5 times, the mixture was placed in a vacuum oven at 60 ° C and dried in the dark for 11 h to obtain a silver neodecanoate precursor;

[0113] S5. 2.5 g of xylene, 2.5 g of terpineol and 6 g of silver neodecanoate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver neodecanoate;

[0114] S6. Dissolve 2.5 g of sodium hydroxide in 50 mL of deionized water to obtain a mixed solution B1;

[0115] S7. Dissolve 10 g of pivalic acid in 50 mL of methanol to obtain a mixed solution B2;

[0116] S8. Dissolve 9.5 g of silver nitrate in 50 mL of deionized water to obtain a mixed solution B3;

[0117] S9. 50 mL of mixed solution B1 was added to 50 mL of mixed solution B2, and the mixture was stirred at room temperature for 30 min. Then, 50 mL of mixed solution B3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol for 5 times, the mixture was placed in a vacuum oven at 60° C. and dried in the dark for 11 h to obtain a silver pivalate precursor.

[0118] S10. 2.5 g of xylene, 2.5 g of terpineol and 6 g of silver pivalate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver pivalate;

[0119] S11. Dissolve 2.5 g of sodium hydroxide in 50 mL of deionized water to obtain a mixed solution C1;

[0120] S12. Dissolve 10 g of n-butyric acid in 50 mL of methanol to obtain a mixed solution C2;

[0121] S13. Dissolve 9.5 g of silver nitrate in 50 mL of deionized water to obtain a mixed solution C3;

[0122] S14. 50 mL of mixed solution C1 was added to 50 mL of mixed solution C2, and the mixture was stirred at room temperature for 30 min. Then 50 mL of mixed solution C3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol for 5 times, the mixture was placed in a vacuum oven at 60 ° C and dried in the dark for 11 h to obtain a silver butyrate precursor;

[0123] S15. 2.5 g of xylene, 2.5 g of pinene alcohol and 6 g of silver butyrate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver butyrate;

[0124] S16. 4.5 g of silver neodecanoate, 3.8 g of silver neopentanoate and 0.7 g of silver n-butyrate were mixed to obtain silver resinate;

[0125] S17. 13 g of silver nanowires having an average diameter of 59 nm and an aspect ratio of 175, 32.5 g of silver nanosheets having a size of 2.5 μm, and 3.5 g of silver nanoparticles having an average particle size of 3.9 nm were mixed to obtain silver nanoparticles;

[0126] S18. Mixing 49 g of nano silver powder and 8.5 g of silver resinate to obtain a composite silver powder;

[0127] S19. 0.3 g of silver nitrate was added to 1.2 mL of 78° C. deionized water to prepare an aqueous solution of silver nitrate, 47 g of polyether polyurethane resin was added to 39 mL of butyl acetate, mechanically stirred for 20 min, 1.3 mL of silver nitrate aqueous solution was added, and stirred for 30 min to obtain a polyether polyurethane silver resin;

[0128] S20. 16 g of a polyether polyurethane silver resin, 14 g of an aqueous polyurethane resin and 8 g of an aqueous acrylate were mixed to obtain an organic carrier;

[0129] S21. 57 g of composite silver powder, 35 g of organic carrier, 5 g of diethylene glycol butyl ether acetate, 1.8 g of copper oxide, 1.5 g of tributyl citrate and 1.5 g of polyamide wax are mixed, ground, and materials with a fineness of less than 10 μm are collected to obtain a conductive silver paste for a low-temperature co-fired ceramic substrate.

[0130] Embodiment 4: A method for preparing a conductive silver paste for a low temperature co-fired ceramic substrate, comprising the following steps:

[0131] S1. Dissolve 2.6 g of sodium hydroxide in 51 mL of deionized water to obtain a mixed solution A1;

[0132] S2. Dissolve 10 g of neodecanoic acid in 51 mL of methanol to obtain a mixed solution A2;

[0133] S3. Dissolve 9.6 g of silver nitrate in 50 mL of deionized water to obtain a mixed solution A3;

[0134] S4. 51 mL of the mixed solution A1 was added to 51 mL of the mixed solution A2, and the mixture was stirred at room temperature for 30 min. Then, 50 mL of the mixed solution A3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol 4 times, the mixture was placed in a vacuum oven at 60 ° C and dried in the dark for 11 h to obtain a silver neodecanoate precursor;

[0135] S5. 2.6 g of xylene, 2.6 g of terpineol and 6.1 g of silver neodecanoate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver neodecanoate;

[0136] S6. Dissolve 2.6 g of sodium hydroxide in 51 mL of deionized water to obtain a mixed solution B1;

[0137] S7. Dissolve 10 g of pivalic acid in 51 mL of methanol to obtain a mixed solution B2;

[0138] S8. Dissolve 9.6 g of silver nitrate in 50 mL of deionized water to obtain a mixed solution B3;

[0139] S9. 51 mL of mixed solution B1 was added to 51 mL of mixed solution B2, and the mixture was stirred at room temperature for 30 min. Then, 50 mL of mixed solution B3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol for 4 times, the mixture was placed in a vacuum oven at 60° C. and dried in the dark for 11 h to obtain a silver pivalate precursor.

[0140] S10. 2.6 g of xylene, 2.6 g of terpineol and 6.1 g of silver pivalate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver pivalate;

[0141] S11. Dissolve 2.6 g of sodium hydroxide in 51 mL of deionized water to obtain a mixed solution C1;

[0142] S12. Dissolve 10 g of n-butyric acid in 51 mL of methanol to obtain a mixed solution C2;

[0143] S13. Dissolve 9.6 g of silver nitrate in 50 mL of deionized water to obtain a mixed solution C3;

[0144] S14. 51 mL of mixed solution C1 was added to 51 mL of mixed solution C2, and the mixture was stirred at room temperature for 30 min. Then, 50 mL of mixed solution C3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol for 4 times, the mixture was placed in a vacuum oven at 60° C. and dried in the dark for 11 h to obtain a silver butyrate precursor.

[0145] S15. 2.6 g of xylene, 2.6 g of pinene alcohol and 6.1 g of silver butyrate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver butyrate;

[0146] S16. 4.6 g of silver neodecanoate, 3.8 g of silver neopentanoate and 0.8 g of silver n-butyrate were mixed to obtain silver resinate;

[0147] S17. 13 g of silver nanowires having an average diameter of 59 nm and an aspect ratio of 175, 32.8 g of silver nanosheets having a size of 2.4 μm, and 3.6 g of silver nanoparticles having an average particle size of 3.9 nm were mixed to obtain silver nanoparticles;

[0148] S18. Mixing 49 g of nano silver powder and 8.6 g of silver resinate to obtain a composite silver powder;

[0149] S19. 0.35 g of silver nitrate was added to 1.3 mL of 78° C. deionized water to prepare an aqueous solution of silver nitrate, 48 g of polyether polyurethane resin was added to 39.2 mL of butyl acetate, mechanically stirred for 20 min, 1.3 mL of silver nitrate aqueous solution was added, and stirred for 30 min to obtain a polyether polyurethane silver resin;

[0150] S20.18g of polyether polyurethane silver resin, 16g of waterborne polyurethane resin and 9g of waterborne acrylate are uniformly mixed to obtain an organic carrier;

[0151] S21. 58 g of composite silver powder, 40 g of organic carrier, 3 g of diethylene glycol butyl ether acetate, 2.8 g of copper oxide, 1.6 g of tributyl citrate and 1.6 g of polyamide wax are mixed, ground, and materials with a fineness of less than 10 μm are collected to obtain a conductive silver paste for a low-temperature co-fired ceramic substrate.

[0152] Embodiment 5: A method for preparing a conductive silver paste for a low temperature co-fired ceramic substrate, comprising the following steps:

[0153] S1. Dissolve 2.8 g of sodium hydroxide in 53 mL of deionized water to obtain a mixed solution A1;

[0154] S2. Dissolve 11 g of neodecanoic acid in 53 mL of methanol to obtain a mixed solution A2;

[0155] S3. Dissolve 9.8 g of silver nitrate in 51 mL of deionized water to obtain a mixed solution A3;

[0156] S4. 53 mL of the mixed solution A1 was added to 53 mL of the mixed solution A2, and the mixture was stirred at room temperature for 30 min. Then, 51 mL of the mixed solution A3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol 4 times, the mixture was placed in a vacuum oven at 60 ° C and dried in the dark for 11 h to obtain a silver neodecanoate precursor;

[0157] S5. 2.8 g of xylene, 2.8 g of terpineol and 6.3 g of silver neodecanoate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver neodecanoate;

[0158] S6. Dissolve 2.8 g of sodium hydroxide in 53 mL of deionized water to obtain a mixed solution B1;

[0159] S7. Dissolve 11 g of pivalic acid in 53 mL of methanol to obtain a mixed solution B2;

[0160] S8. Dissolve 9.8 g of silver nitrate in 51 mL of deionized water to obtain a mixed solution B3;

[0161] S9. 53 mL of mixed solution B1 was added to 53 mL of mixed solution B2, and the mixture was stirred at room temperature for 30 min. Then, 51 mL of mixed solution B3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol for 4 times, the mixture was placed in a vacuum oven at 60° C. and dried in the dark for 11 h to obtain a silver pivalate precursor.

[0162] S10. 2.8 g of xylene, 2.8 g of terpineol and 6.3 g of silver pivalate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver pivalate;

[0163] S11. Dissolve 2.8 g of sodium hydroxide in 53 mL of deionized water to obtain a mixed solution C1;

[0164] S12. Dissolve 11 g of n-butyric acid in 53 mL of methanol to obtain a mixed solution C2;

[0165] S13. Dissolve 9.8 g of silver nitrate in 51 mL of deionized water to obtain a mixed solution C3;

[0166] S14. 53 mL of mixed solution C1 was added to 53 mL of mixed solution C2, and the mixture was stirred at room temperature for 30 min. Then, 51 mL of mixed solution C3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol for 4 times, the mixture was placed in a vacuum oven at 60° C. and dried in the dark for 11 h to obtain a silver butyrate precursor.

[0167] S15. 2.8 g of xylene, 2.8 g of pinene alcohol and 6.3 g of silver butyrate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver butyrate;

[0168] S16. 4.8 g of silver neodecanoate, 3.9 g of silver neopentanoate and 0.9 g of silver n-butyrate were mixed to obtain silver resinate;

[0169] S17. 13 g of silver nanowires having an average diameter of 59 nm and an aspect ratio of 175, 32.8 g of silver nanosheets having a size of 2.5 μm, and 3.5 g of silver nanoparticles having an average particle size of 3.9 nm were mixed to obtain silver nanoparticles;

[0170] S18. 50 g of nano silver powder and 8.8 g of silver resinate were mixed to obtain a composite silver powder;

[0171] S19. 0.35 g of silver nitrate was added to 1.4 mL of 79° C. deionized water to prepare an aqueous solution of silver nitrate, 49 g of polyether polyurethane resin was added to 39 mL of butyl acetate, mechanically stirred for 20 min, 1.4 mL of silver nitrate aqueous solution was added, and stirred for 30 min to obtain a polyether polyurethane silver resin;

[0172] S20. 20 g of polyether polyurethane silver resin, 18 g of aqueous polyurethane resin and 11 g of aqueous acrylate were mixed to obtain an organic carrier;

[0173] S21. 59 g of composite silver powder, 50 g of organic carrier, 4 g of diethylene glycol ethyl ether acetate, 2.9 g of zinc oxide, 1.8 g of tributyl citrate and 1.8 g of polyamide wax are mixed, ground, and materials with a fineness of less than 10 μm are collected to obtain a conductive silver paste for a low-temperature co-fired ceramic substrate.

[0174] Embodiment 6: A method for preparing a conductive silver paste for a low temperature co-fired ceramic substrate, comprising the following steps:

[0175] S1. Dissolve 3 g of sodium hydroxide in 55 mL of deionized water to obtain a mixed solution A1;

[0176] S2. Dissolve 12 g of neodecanoic acid in 55 mL of methanol to obtain a mixed solution A2;

[0177] S3. Dissolve 10 g of silver nitrate in 52 mL of deionized water to obtain a mixed solution A3;

[0178] S4. 55 mL of the mixed solution A1 was added to 55 mL of the mixed solution A2, and the mixture was stirred at room temperature for 30 min, and then 52 mL of the mixed solution A3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol for 5 times, the mixture was placed in a vacuum oven at 60 ° C and dried in the dark for 12 h to obtain a silver neodecanoate precursor;

[0179] S5. 3 g of xylene, 3 g of terpineol and 6.5 g of silver neodecanoate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver neodecanoate;

[0180] S6. Dissolve 3 g of sodium hydroxide in 55 mL of deionized water to obtain a mixed solution B1;

[0181] S7. Dissolve 12 g of pivalic acid in 55 mL of methanol to obtain a mixed solution B2;

[0182] S8. Dissolve 10 g of silver nitrate in 52 mL of deionized water to obtain a mixed solution B3;

[0183] S9. 55 mL of mixed solution B1 was added to 55 mL of mixed solution B2, and the mixture was stirred at room temperature for 30 min. Then, 52 mL of mixed solution B3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol for 5 times, the mixture was placed in a vacuum oven at 60° C. and dried in the dark for 12 h to obtain a silver pivalate precursor.

[0184] S10. 3 g of xylene, 3 g of terpineol and 6.5 g of silver pivalate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver pivalate;

[0185] S11. Dissolve 3 g of sodium hydroxide in 55 mL of deionized water to obtain a mixed solution C1;

[0186] S12. Dissolve 12 g of n-butyric acid in 55 mL of methanol to obtain a mixed solution C2;

[0187] S13. Dissolve 10 g of silver nitrate in 52 mL of deionized water to obtain a mixed solution C3;

[0188] S14. 55 mL of mixed solution C1 was added to 55 mL of mixed solution C2, and the mixture was stirred at room temperature for 30 min. Then, 52 mL of mixed solution C3 was added, and the mixture was stirred for another 30 min. After filtering and washing with ethanol for 5 times, the mixture was placed in a vacuum oven at 60 ° C and dried in the dark for 12 h to obtain a silver butyrate precursor;

[0189] S15. 3 g of xylene, 3 g of pinene alcohol and 6.5 g of silver butyrate precursor were placed in a glass bottle, and the resulting solution was filtered with a 200 μm syringe filter to obtain silver butyrate;

[0190] S16. 5 g of silver neodecanoate, 4 g of silver neopentanoate and 1 g of silver butyrate were mixed to obtain silver resinate;

[0191] S17. 14 g of silver nanowires having an average diameter of 60 nm and an aspect ratio of 175, 33 g of silver nanosheets having a size of 3 μm, and 4 g of silver nanoparticles having an average particle size of 4 nm were mixed to obtain silver nanoparticles;

[0192] S18. Mixing 51 g of nano silver powder and 9 g of silver resinate to obtain a composite silver powder;

[0193] S19. 0.4 g of silver nitrate was added to 1.5 mL of 80° C. deionized water to prepare an aqueous solution of silver nitrate, 50 g of polyether polyurethane resin was added to 40 mL of butyl acetate, mechanically stirred for 20 min, 1.5 mL of silver nitrate aqueous solution was added, and stirred for 30 min to obtain a polyether polyurethane silver resin;

[0194] S20. 22 g of polyether polyurethane silver resin, 20 g of aqueous polyurethane resin and 13 g of aqueous acrylate were mixed to obtain an organic carrier;

[0195] S21. 60 g of composite silver powder, 55 g of organic carrier, 22 g of pine alcohol, 5 g of aluminum oxide, 2 g of tributyl citrate and 2 g of polyamide wax are mixed, ground, and materials with a fineness of less than 10 μm are collected to obtain a conductive silver paste for a low-temperature co-fired ceramic substrate.

[0196] Comparative Example 1:

[0197] Compared with Example 1, this comparative example does not add silver neodecanoate during the preparation of the conductive silver paste. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a conductive silver paste is obtained.

[0198] Comparative Example 2:

[0199] Compared with Example 1, this comparative example does not add silver pivalate during the preparation of the conductive silver paste, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a conductive silver paste is obtained.

[0200] Comparative Example 3:

[0201] Compared with Example 1, this comparative example does not add silver butyrate during the preparation of the conductive silver paste. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a conductive silver paste is obtained.

[0202] Comparative Example 4:

[0203] Compared with Example 1, this comparative example only adjusts the amount of silver neodecanoate from 4 g to 0.5 g, and the amount of n-butyric acid from 0.5 g to 4 g, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a conductive silver paste is obtained.

[0204] Comparative Example 5:

[0205] Compared with Example 1, this comparative example does not add silver resinate during the preparation of the conductive silver paste, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a conductive silver paste is obtained.

[0206] Comparative Example 6:

[0207] Compared with Example 1, in this comparative example, no nanosilver wires and nanosilver sheets were added during the preparation of the conductive silver paste. The remaining steps and parameters were the same and will not be repeated in this comparative example. Finally, a conductive silver paste was obtained.

[0208] Comparative Example 7:

[0209] In this comparative example and Example 1, only the amount of nanosilver flakes is adjusted from 23g to 3g, and the amount of nanosilver particles is adjusted from 2g to 32g. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a conductive silver paste is obtained.

[0210] Comparative Example 8:

[0211] In this comparative example and Example 1, no polyether polyurethane silver resin was added during the preparation of the conductive silver paste. The remaining steps and parameters were the same and will not be repeated in this comparative example. Finally, a conductive silver paste was obtained.

[0212] Comparative Example 9:

[0213] Compared with Example 1, this comparative example only adjusts the amount of polyether polyurethane silver resin from 12g to 4g, and the amount of water-based acrylate from 4g to 12g, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally obtains a conductive silver paste.

[0214] Performance Testing:

[0215] Resistivity test:

[0216] Resistivity is a physical quantity used to characterize the conductivity of a material. The conductivity test method of conductive silver paste is as follows: First, apply the prepared silver paste to a glass slide to make a conductive circuit, then vacuum cure it at 160°C for 2 hours, and finally use an RTS-9 dual-electrical four-probe tester to test the surface resistivity of the cured silver paste;

[0217] Adhesion test:

[0218] Adhesion is an important indicator to characterize and measure the performance of conductive silver paste. When the adhesion is low, the silver paste film is prone to blistering and falling off, making it difficult to achieve effective connection between electronic components or devices. This experiment uses the hundred-grid knife tester (QFH-A) of Quzhou Aipu Metrology Instrument Co., Ltd. for testing. The test method is carried out in accordance with "GB9286-88 Cross-grid Test for Paint and Varnish Film". First. Place the glass substrate coated with silver paste on a flat and hard surface, and use a hundred-grid knife to make a vertical cut with a 90° cross scratch. The cutting tool should form a 10×10 grid pattern with a specified interval on the coating with uniform force and speed, and then use a soft brush to brush back and forth along the diagonal direction of the grid several times to remove paint chips. Finally, place the center point of the standard 75mm transparent pressure-sensitive tape on the grid, parallel to a set of cutting lines, flatten the part of the tape on the grid with your fingers, and press the tape with your fingertips to ensure good contact between the tape and the coating. Within 5 minutes, peel off the tape smoothly within 0.5-1.0s at an angle close to 60°. Table 1 below is the adhesion evaluation standard. When the adhesion level of the sample is at level 0 and level 1, the 100-grid test is qualified. Record the adhesion when the curing temperature is 160℃ and 200℃;

[0219] Pencil hardness test:

[0220] Pencil hardness is the resistance of conductive silver paste to foreign objects invading its surface, which is one of the important properties of the mechanical strength of conductive silver paste. In this experiment, the hardness tester (QFH-A) of Quzhou Aipu Metrology Instrument Co., Ltd. was used, and the hardness test method was carried out according to the national standard "GB / T6739-2006 Paint and Varnish Pencil Method for Determination of Paint Film Hardness". First, place the painted sample on a horizontal and stable surface, keep the instrument horizontal, insert the prepared pencil into the pencil hardness tester and fix it. Then, according to the requirements of the national standard, load the weight to the pencil load (1.00±0.05kg). Finally, place the tip of the pencil on the surface of the paint film to be tested. When the tip of the pencil contacts the paint film coating, push the test plate at a speed of 0.5-1mm / s and push it at least 7mm away from the operator. The hardness grade judgment standard is: the hardness of the paint film coating is expressed by the hardness of the hardest pencil that does not cause scratches of 3m or more on the paint film coating, and the hardness is recorded at the curing temperature of 160℃ and 200℃;

[0221] The results are shown in Table 2 below:

[0222] Table 1 Evaluation criteria for paint film adhesion

[0223] ;

[0224] Table 2 Summary of experimental results of Examples 1 to 6 and Comparative Examples 1 to 9

[0225] ;

[0226] Data Analysis:

[0227] It can be seen from Table 1 that the conductive silver paste prepared by the present invention has better conductivity, higher hardness and better adhesion.

[0228] This may be because the compounding of silver resinate and organic carrier can form a conductive network inside the system. At the same time, the compounding of nanosilver wires, nanosilver flakes and silver nanoparticles of different dimensions in the nanosilver powder can increase the conductive pathway inside the system and increase the conductive effect of the conductive silver paste finally obtained. The introduction of silver neodecanoate, silver neopentanoate and butyric acid in the silver resinate can synergize with the polyether polyurethane silver resin. During the curing temperature increase process, as the temperature of the components increases, the organic carrier will gradually begin to shrink, which will form a cross-linked network inside the system, thereby reducing the distance between the composite silver powders, making the composite silver powder particles in close contact, and the organic carrier and the equipment are closely attached, so that the conductive silver paste finally obtained has good conductivity and good adhesion and hardness.

[0229] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0230] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A conductive silver paste for a low temperature co-fired ceramic substrate, characterized in that: The method comprises the following raw materials in parts by weight: 40-60 parts of composite silver powder, 26-55 parts of organic carrier, 2-5 parts of solvent, 0.5-5 parts of inorganic additive, 0.5-2 parts of plasticizer and 0.5-2 parts of thixotropic agent; The composite silver powder is nano silver powder and silver resinate in a mass ratio of 32-51:8-9; The nano silver powder is obtained by mixing nano silver wires, nano silver flakes and nano silver particles in a mass ratio of 7-14:23-33:2-4; The average diameter of the silver nanowires is 58-60 nm and the aspect ratio is 175; The size of the nano silver flakes is 2-3 μm; The average particle size of the nano silver particles is 3.8-4 nm; The silver resinate is obtained by mixing silver neodecanoate, silver neopentanoate and silver butyrate in a mass ratio of 4-5:3.5-4:0.5-1; The organic carrier is obtained by mixing polyether polyurethane silver resin, waterborne polyurethane resin and waterborne acrylate resin in a mass ratio of 12-22:10-20:4-13; The preparation method of the polyether polyurethane silver resin is as follows: 45-50 g of polyether polyurethane resin was added to 38-40 mL of butyl acetate, mechanically stirred for 20 min, 1-1.5 mL of silver nitrate aqueous solution was added, and stirred for 30 min to obtain polyether polyurethane silver resin; The aqueous solution of silver nitrate is prepared by adding 0.2-0.4 g of silver nitrate into 1-1.5 mL of 75-80° C. deionized water.

2. The conductive silver paste for low temperature co-fired ceramic substrate according to claim 1, characterized in that: The preparation method of the silver neodecanoate is as follows: Step A1. Dissolve sodium hydroxide in deionized water to obtain a mixed solution A1; Step A2. dissolving neodecanoic acid in methanol to obtain a mixed solution A2; Step A3. Dissolve silver nitrate in deionized water to obtain a mixed solution A3; Step A4. Add the mixed solution A1 to the mixed solution A2, stir and react at room temperature for 30 minutes, then add the mixed solution A3, stir for another 30 minutes, filter, wash with ethanol 3-5 times, and place in a vacuum oven at 60°C to dry in the dark for 10-12 hours to obtain a silver neodecanoate precursor; Step A5. xylene, pineol and silver neodecanoate precursor are placed in a glass bottle, and finally the obtained solution is filtered through a 200 μm syringe filter to obtain silver neodecanoate.

3. The conductive silver paste for low temperature co-fired ceramic substrate according to claim 2, characterized in that: The ratio of sodium hydroxide to deionized water in step A1 is 2-3 g: 45-55 mL; The ratio of neodecanoic acid to methanol in step A2 is 8-12 g: 45-55 mL; The usage ratio of silver nitrate and deionized water in step A3 is 9-10 g:48-52 mL; In step A4, the volume ratio of the mixed solution A1, the mixed solution A2 and the mixed solution A3 is 45-55:45-55:48-52; The mass ratio of xylene, terpineol and silver neodecanoate precursor in step A5 is 2-3:2-3:5.5-6.

5.

4. The conductive silver paste for low temperature co-fired ceramic substrate according to claim 1, characterized in that: The preparation method of the silver pivalate is as follows: Step B1. Dissolve sodium hydroxide in deionized water to obtain a mixed solution B1; Step B2. dissolving pivalic acid in methanol to obtain a mixed solution B2; Step B3. Dissolve silver nitrate in deionized water to obtain a mixed solution B3; Step B4. Add the mixed solution B1 to the mixed solution B2, stir and react at room temperature for 30 minutes, then add the mixed solution B3, stir for another 30 minutes, filter, wash with ethanol 3-5 times, and place in a vacuum oven at 60° C. to dry in the dark for 10-12 hours to obtain a silver pivalate precursor; Step B5. xylene, pinene alcohol and silver pivalate precursor are placed in a glass bottle, and finally the obtained solution is filtered through a 200 μm syringe filter to obtain silver pivalate.

5. The conductive silver paste for low temperature co-fired ceramic substrate according to claim 4, characterized in that: The ratio of sodium hydroxide to deionized water in step B1 is 2-3 g: 45-55 mL; The ratio of pivalic acid to methanol in step B2 is 8-12 g: 45-55 mL; The usage ratio of silver nitrate and deionized water in step B3 is 9-10 g: 48-52 mL; In step B4, the volume ratio of the mixed solution B1, the mixed solution B2 and the mixed solution B3 is 45-55:45-55:48-52; The mass ratio of xylene, terpineol and silver pivalate precursor in step B5 is 2-3:2-3:5.5-6.

5.

6. The conductive silver paste for low temperature co-fired ceramic substrate according to claim 1, characterized in that: The preparation method of the silver n-butyrate is as follows: Step C1. dissolving sodium hydroxide in deionized water to obtain a mixed solution C1; Step C2. dissolving n-butyric acid in methanol to obtain a mixed solution C2; Step C3. dissolving silver nitrate in deionized water to obtain a mixed solution C3; Step C4. Add the mixed solution C1 to the mixed solution C2, stir and react at room temperature for 30 minutes, then add the mixed solution C3, stir for another 30 minutes, filter, wash with ethanol 3-5 times, and place in a vacuum oven at 60° C. to dry in the dark for 10-12 hours to obtain a silver butyrate precursor; Step C5. xylene, pinene alcohol and silver butyrate precursor are placed in a glass bottle, and finally the obtained solution is filtered through a 200 μm syringe filter to obtain silver butyrate.

7. The conductive silver paste for low temperature co-fired ceramic substrate according to claim 6, characterized in that: The ratio of sodium hydroxide to deionized water in step C1 is 2-3 g: 45-55 mL; The usage ratio of n-butyric acid and methanol in step C2 is 8-12 g: 45-55 mL; The usage ratio of silver nitrate and deionized water in step C3 is 9-10 g: 48-52 mL; In step C4, the volume ratio of the mixed solution C1, the mixed solution C2 and the mixed solution C3 is 45-55:45-55:48-52; The mass ratio of xylene, terpineol and silver butyrate precursor in step C5 is 2-3:2-3:5.5-6.

5.

8. The conductive silver paste for low temperature co-fired ceramic substrate according to claim 1, characterized in that: The solvent is any one of diethylene glycol ethyl ether, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, diethylene glycol ethyl ether acetate and terpineol; The inorganic additive is any one of magnesium oxide, titanium dioxide, copper oxide, zinc oxide and aluminum oxide; The plasticizer is tributyl citrate; and the thixotropic agent is polyamide wax.

9. The method for preparing a conductive silver paste for a low temperature co-fired ceramic substrate according to any one of claims 1 to 8, characterized in that: The following steps are involved: The composite silver powder, organic carrier, solvent, inorganic additive, plasticizer and thixotropic agent are mixed, ground, and materials with a fineness of less than 10 μm are collected to obtain a conductive silver paste for a low-temperature co-fired ceramic matrix.

Citation Information

Patent Citations

  • Silver oxide slurry for electronic component and preparation method

    CN112712913A

  • Sintered silver paste, sintered silver film preformed sheet and application of sintered silver paste and sintered silver film preformed sheet

    CN117497224A